2010
DOI: 10.1007/s10800-010-0250-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of N2-fixation on polyaniline electrodes in methanol by electrochemical impedance spectroscopy

Abstract: The ac response of polyaniline thin films on platinum electrodes was measured at different dc potentials during the N 2 -fixation in methanol ? LiClO 4 electrolyte with 0.03 mol L -1 H 2 SO 4 for the first time. The optimum film thickness was found to be 1.5 lm, N 2 -pressure 50 bar and an optimum electrolysis potential of -0.12 V (NHE). The diffusion coefficients for N 2 into the polymer film was found to be (5 ± 2)910 -9 cm 2 s -1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…From EIS and Tafel analyses in the methanol solution, the authors suggested that ammonia was formed by successive addition of *H atoms, which were formed by the electroreduction of protons, to the adsorbed N 2 molecules on the polyaniline film. 304 This mechanism was similar to the one the authors suggested for N 2 reduction in the aqueous solution. 235 N 2 electroreduction in 2-propanol 305 and ethylenediamine 306 was examined by Kim et al In the first case, 305 the electrolyte was a mixture of 2propanol and deionized water (9:1, v/v) with 10 mM H 2 SO 4 as a supporting electrolyte, and a porous nickel electrode was used as the cathode (Figure 39d).…”
Section: N 2 Electroreduction In Nonaqueous Solventssupporting
confidence: 82%
See 1 more Smart Citation
“…From EIS and Tafel analyses in the methanol solution, the authors suggested that ammonia was formed by successive addition of *H atoms, which were formed by the electroreduction of protons, to the adsorbed N 2 molecules on the polyaniline film. 304 This mechanism was similar to the one the authors suggested for N 2 reduction in the aqueous solution. 235 N 2 electroreduction in 2-propanol 305 and ethylenediamine 306 was examined by Kim et al In the first case, 305 the electrolyte was a mixture of 2propanol and deionized water (9:1, v/v) with 10 mM H 2 SO 4 as a supporting electrolyte, and a porous nickel electrode was used as the cathode (Figure 39d).…”
Section: N 2 Electroreduction In Nonaqueous Solventssupporting
confidence: 82%
“…As has been introduced in section , the same group used a Pt plate coated with a polypyrrole film as an electrode material for N 2 reduction in an aqueous solution containing 0.1 M Li 2 SO 4 and 0.03 M H + , and under a N 2 pressure of 6 MPa . Comparing these two examples, they produced similar amounts of ammonia under the optimum conditions; however, CV scans showed that the current density in the aqueous solution was more than three times larger than that in the methanol solution. , This indicates that a significantly higher Faradaic efficiency was obtained in the methanol solution than in the aqueous solution. From EIS and Tafel analyses in the methanol solution, the authors suggested that ammonia was formed by successive addition of *H atoms, which were formed by the electroreduction of protons, to the adsorbed N 2 molecules on the polyaniline film .…”
Section: Electrocatalytic Reduction Of N2 To Ammonia At Low Temperatu...mentioning
confidence: 99%
“…These possibilities are illustrated in Figure a,b. There are attempts in the literature to suppress hydrogen evolution for a range of applications, both via reducing the number of proton donors , and through the use of a protection layer to hinder proton transport. It may also be possible to reduce the effective proton concentration near the surface ( c̃ + ), without changing the number of proton donors, through a solvent with slow proton transfer kinetics from the bulk. It has been shown, for example, that more sterically bulky proton donor molecules exhibit considerably slower proton transfer in nonaqueous electrolytes .…”
mentioning
confidence: 99%
“…Experimentally, we had found that the amount of ammonia produced from N 2 depends strongly on the potential applied and the electrode material employed in the acidic aqueous medium. 5,6,18 The H ad formation on a blank Pt surface was expected (depending on the pH value of the solution) at overpotentials between -0.1 and -0.3 V. 21 Because the Pt plate acts as a supporting material for porous polymer film, it is expected that the H ad formation needs to occur at potential values characteristic for Pt in acidic aqueous solutions. Based on these facts, the previous preparative experiments were carried out at potentials between -0.100 and -0.350 V in 0.025 V steps and the maximum ammonia was formed at ca.…”
Section: The Effect Of Applied Potentials On Impedance Measurementsmentioning
confidence: 99%
“…The results of preparative electrolyses in our previous study confirm the impedance spectroscopic findings presented in the present study. 5 The sum of two resistances, R 1 (resistance of the film) and R 2 (related to reduction kinetics), give an idea about the overall reaction, and the potential dependence of -log (R 1 + R 2 ) provides an EIS-Tafel diagram (Figure 9), which can be used for kinetic data derived from the Tafel equation: 6,33 η= a + blogj, (6) where η represents the applied potential, j is the exchange current density, and b is the Tafel slope defined as b = −2.303RT /αnF (7) In the Tafel slope equation, α is the transfer coefficient, n is the number of transferred electrons, R (8.314 J K −1 mol −1 ) is the gas constant, and F (96,487 C mol −1 ) is the Faraday constant. The calculated exchange current density ( j) value is 3.17 10 −3 A cm −2 .…”
Section: Evaluation Of Eis Data and Reaction Mechanismmentioning
confidence: 99%